(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Arobaya AYS, Zuhud EAM, Siregar IZ, Irawati. 2022. Short Communication: Diversity and distribution of epiphytic orchid Dendrobium section Spatulata on the host plants in the Cycloop Mountain Nature Reserve of Papua, Indonesia. Biodiversitas 23: 2025-2034. Knowledge of species diversity and distribution is indispensable to assist in formulating a sound conservation strategy. This is truly significant for epiphytic orchids that grow on tree surfaces or phorophyte. The data and information are still limited despite their important role as biological indicators in forest ecosystems. The aim of the study was to carry out an inventory of epiphytic orchids and the phorophytes (host tress) in the Tropical Rain Forest of Cycloop Mountain Nature Reserve. The study took place in four sites located in the regency and city of Jayapura. Exploratory and sampling strip methods of 20x100 square meters were employed during the fieldwork. Orchids were observed and samples were collected based on their distribution in the host plants divided into five zones (Stem zone I and II; Crown zone III to V). The habitat’s vegetation profiles were described using computer-aided design (CAD) verse 2018. Plant samples were identified in herbarium Manokwariense and the identified species were incorporated into CAD. Nineteen species of Dendrobium section Spatulata were identified as living as an epiphyte on the 12 phorophytes. These orchids and the host plants were described, determined and analyzed using PATN software. Most orchids are growing abundant in zone II and III. The phorophytes hosting the orchids in the lowland are mainly Syzygium and Intsia, while in the highland are Agathis and Podocarpus. Two types of vegetation profiles were described as savannah woodland in the low land area and coniferous trees vegetation in the highland above 650 m above sea level.